Production and marketing process assistance of MSMEs Dedy's Babies Wear - Yepy Komaril Sofi'i; Sudarman Sudarman; Rr Heni Hendaryati; Willy Satrio Nugroho (Universitas Muhammadiyah Magelang, 2023)
MSMEs Dedy's Babies Wear, in its production process, still uses conventional sewing machines, and it causes the production of baby hats and shoes to be limited. Within a month, Dedy's Babies Wear MSMEs could only produce 2400 sets of baby hats and shoes with the help of 5 workers. A group of baby hats and shoes sells for IDR 10,000. In addition, the product marketing process is only limited to local coverages. As a result, market demand is unstable every month. This community service program aims to overcome the partners' main problems (the low production capacity and limited marketing process). This program is carried out with the stages of observation, training, and assistance in sewing with overlocking machines, as well as digital product marketing assistance through the e-commerce platform. From the evaluation, the production of MSMEs capacity has doubled. In addition, customer orders through e-commerce have become a potential source of income for partners.